Does sugar craving predict sugar intake? A preliminary finding from the Sugar Craving Assessment Tool (SCAT) - Wan Mahmood, Wan Fathin Fariza; Mamat, Nik Mazlan; Mat Sahari, Nurfaraheen; Mohd Abu Bakar, Wan Azdie; Safii, Nik Shanita (2014)
Sugar is the most craved form of food in human. Excessive sugar intake has been identified to be causative of unnecessary weight gain and intensify the obesity prevalence around the world. This study aims to 1) investigate the association of Body Mass Index (BMI), sugar craving and sugar intake and 2) to assess the usefulness of the ‘Sugar Craving Assessment Tool (SCAT)’ in predicting sugar consumption in adults. Subjects (N=100, mean age= 21.2 ±1.6 y) were asked to complete 2 types of questionnaires; the Sugar Craving Assessment Tool (SCAT) and the Food Frequency Questionnaire for Sugar. Basic information (gender, age, reported weight and height) were also documented. The responses were analysed and results were presented as BMI, sugar craving scores (0 to 120) and daily sugar intake (g/day). Sugar craving scores were significantly correlated with sugar intake (r=0.321, p=0.001) but neither significant for BMI and sugar craving (r=0.139) nor BMI and sugar intake (r=0.075). Sweetened beverages contributed the highest in daily sugar intake (72.7%) and were the most craved food item (30.5%), followed by confectionery and desserts, cakes and pastries. In conclusion, the higher the sugar craving intensity, the higher the likelihood to increase sugar intake in daily food consumption. The SCAT is beneficial in predicting sugar intake in adults in terms of its administration and analysis, however further study is needed to increase its magnitude of association.